The innocents (1961) and In October there are no miracles (1965), by Oswaldo Reynoso: lexicographical study of novel sexual euphemisms and dysphemisms - Quispe Mendivil, Yoselin (2022)
This lexicographic study defines the novel euphemisms and dysphemisms in the sexual field present in the novels Los inocentes (‘The innocents’) (1961) and En octubre no hay milagros (‘In October there are no miracles’) (1965), by Oswaldo Reynoso. This, in order to contribute to the research on sexual euphemisms and dysphemisms in Peruvian literature. These novels have been chosen as a corpus of study because they present a profusion of euphemistic and dysphemistic sexual terms that represent the popular language of Lima youth in the 1960s. In addition, presents the definitions of the sexual euphemisms and dysphemisms, including simple and compound words, which are not recorded in the Diccionario de americanismos en línea (DA) 2010 or in the Diccionario de la lengua española en línea (DLE) 2021. Most of these words allude to genital organs, non-heteronormative sexual relations, as well as to characters marginalized by Lima society (homosexuals and prostitutes).